Development of a volatile organic compounds cryogenic condensation recovery system cooled by liquid nitrogen. Issue 1 (1st May 2022) - Xu, Hao; Xi, Xiaotong; Xu, Xiafan; Guo, Jia; Chen, Liubiao; Ji, Wei; Wang, Junjie
Abstract: Volatile organic compounds (VOCs) are important precursors of ozone and PM2.5, and the reduction of VOCs emission is a key to control ozone and PM2.5 pollutions. For high-value VOCs such as oil gas, the cryogenic condensation method based on liquid nitrogen cooling is an effective way to recover VOCs. This method can achieve a refrigeration temperature of -170°C or even lower so that the treated exhaust gas concentration can satisfy the emission standard. In this paper, a thermodynamic model is established to calculate and analyze a designed three-stage condensation recovery VOCs system process based on liquid nitrogen cooling. A set of experimental equipment was further developed and tested. And the system process, calculation results, and experimental results are introduced.